Incidence and risk factors for hospital-acquired cholecystitis. (October 2022) - Ito, H.; Watanabe, A.; Okaya, S.; Ogawa, R.; Shimojo, N.
Summary: Background: Acute cholecystitis can occur both inside and outside hospital settings. However, little is known about the clinical characteristics of hospital-acquired cholecystitis (HAC). Aim: To investigate the clinical characteristics of HAC in a tertiary academic hospital. Methods: This retrospective cohort study included hospitalized patients who were found to have gallstones without cholecystitis or cholangitis on admission between January 2018 and December 2021. Multi-variate logistic regression analysis was used to make comparisons between patients with and without HAC. Findings: In total, 890 patients met the inclusion criteria and were evaluated in this study. Forty-one patients (4.6%) developed HAC during the study period. Multi-variate logistic regression analysis showed that a history of cholecystitis or cholangitis, fasting for ≥1 day, and gallstones in the gallbladder neck were independently associated with increased risk of HAC. HAC occurred most frequently after several weeks of admission, and only four patients (9.8%) had bacteraemia. Conclusions: HAC was relatively common among hospitalized patients. Physicians should be aware of the possibility of HAC in symptomatic hospitalized patients with certain risk factors.